NEW-GENERATION STAINLESS STEEL SYSTEMS FOR METALLURGICAL PRODUCTION - A. I. Zolotukhin; A. G. Golovko; E. I. Gordeev; D. А. Provotorov (Литьë и металлургия, 2018)
The article deals with the development of devices for mechanization and automation of metal flow control – steel-pouring ladles sliding gates of the new generation of Vulkan-TM production, the history of their production.The various technical solutions underlying the creation of the sliding gates of the «VT» series, innovative solutions used in design of the sliding gates layouts and their competitive advantages are shown.The design and operation principle of the new development – the device for gas-dynamic protection of the metal stream from secondary oxidation is described.